Influence of Peripartum Supplementation of Rumen Protected Choline and Rumen Protected Fat on Blood Biochemical Profile and Postpartum Reproductive Performance in Gir Cows - Chavda, Miteshkumar R.; Savsani, Harish H.; Karangiya, Vijay K.; Belim, Saman Y.; Kansagara, Yash G.; Javia, Bhavesh B.; Kalariya, Vinay A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted on 24 advanced pregnant Gir cows in their first to third lactation to evaluate the effects of supplementing rumen protected choline (RPC) and rumen protected fat (RPF) alone or in combination on various blood biochemical parameters and postpartum reproductive performance. The cows were divided into four equal treatment groups (n=6 each), viz., T1 (control), T2 (RPC), T3 (RPF) and T4 (RPC and RPF), based on their parity, body weight and previous lactation yield. In T1 group, cows were fed with basal diet to meet their nutrient requirement as per ICAR (2013) feeding standards. In T2 group, cows were supplemented with RPC @ 45 g/day, in T3 with RPF @ 80 g/d and in T4 with RPC @ 45 g/day + RPF @ 80 g/d along with basal diet of T1 starting from 30 days before expected date of calving to 60 days postpartum and blood samples were collected at monthly intervals. Supplementation of RPC and RPF alone or in combination had no significant effect on plasma BUN, cholesterol, TAG, VLDL, NEFA and BHBA levels. Days to first observed heat were reduced significantly (p<0.001), while service period and number of services per conception were reduced non-significantly in supplemented groups compared to control. There was no advantage of combined supplementation of RPC and RPF in periparturient Gir cows. It was concluded that RPC or RPF alone can be supplemented in the ration of periparturient Gir cows to optimize the blood biochemical profile and improve postpartum reproductive performance.